P.035 Health System Utilization and Medication Use among Adults with Migraine in Alberta: An observational cohort study using Alberta administrative health data. (November 2021) - Rajapakse, T; Kassiri, J; Mailo, J; Nabipoor, M; Bakal, J; Richer, L
Abstract : Background: Migraine is costly to governments. Despite significant burden, Canada lacks population data regarding migraine prevalence, resource and medication utilization. We sought to characterize the demographics, health resource utilization, and medication use in an adult migraine cohort in Alberta. Methods: Migraine cohort: previously validated case definition of migraine (ICD 10 + dispensation of abortive and/or preventative migraine drug (04/2010-03/2016). Patients over 18 years, followed three years from index date [first dispensation of migraine medication]. Health resource utilization (HRU) assessed by emergency department (ED) visits, hospital admission and physician claims. Medication assessed province-wide dispensation database linkage. Patient demographics and Charlson Comorbidity Index (CCI) included. Results: Over 5 years: 53, 333 migraine cases identified (mean age 40.5 years, 79% female). Common comorbidities: hypertension, COPD, diabetes mellitus, cancer, cerebrovascular disease. Mean CCI 0.55 (SD 1.06). Metropolitan patients: 48%, urban 34.6%, rural 17.4%. Initial migraine diagnosis: 46% by GP, 31% in ED. Rural patients present more to ED/hospital for care in 3-year follow-up (IRR 2.95 [2.83, 3.08]). Conclusions: Our migraine case definition is more specific than sensitive and underestimates Alberta's migraine prevalence. Higher female prevalence as expected. Rurally, migraine care largely occurs in ED/hospital. Study of prevalence, HRU and medications may help inform health policy in Alberta and Canada.